Synthesis and Characterization of Complex Compounds of Cadmium (II) Nitrate, Potassium Thiocyanate, and 2,2-Bipyridine Ligand - Faqih, Khoirul; Rong Cao; Saeed Ahmad; Muntholib, Muntholib (Tinta Emas Publisher, 2023)
A complex compound of a central atom of cadmium(II), potassium thiocyanate, and a 2,2'-bipy ligand with a stoichiometric ratio of 1:2:2 has never been reported. The aim of this research is to determine the coordination pattern of the 2,2'-bipy ligand and thiocyanate ion and the stability of the compounds formed. Synthesis of complex compounds was carried out using the direct reaction method, characterization of the complex compounds produced using the melting point test, FTIR analysis, SEM-EDX analysis, DHL test, thiocyanate ion qualitative test, and Gaussian 09W analysis. This synthesis produces a block-shaped colorless complex compound with a melting point of 159-161°C and has a distorted tetrahedral geometry around the central cadmium(II) atom and a free energy of -740 kJ/mol and a free energy per bond of -25 kJ/ mol.